Climate mitigation and human comfort – A decision-support modeling and simulation tool - Roberta Zarcone; Federica Nava; Fabrizio Tucci (Agathón)
Human activities are recognised as primarily responsible for global warming, with consequences such as biodiversity loss and extreme weather phenomena that impact human well-being. This study proposes a methodological approach for numerical simulation of the interactions between climate phenomena, the built environment, and the individual, based on the assumption that thoroughly understanding these connections will enable the development of more effective intervention strategies for climate mitigation and human comfort. The methodology is applied to three pilot cases in order to analyse the influence of different parameters of the urban built environment on physiological stress: the Quarticciolo neighbourhood (former borough) in Rome (Italy), the Westside San Antonio neighbourhood in Texas (USA), and the Shuangta Suzhou neighbourhood in China.